2007
DOI: 10.1891/088667007781554008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Mothers’ Social Networks and Severe Domestic Violence: A Test of the Social Isolation Hypothesis

Abstract: To understand the relationship between characteristics of mothers' social networks and domestic violence, battered mothers who were severely assaulted were compared to battered mothers who were not severely assaulted and mothers who were not assaulted. The results showed that all three groups of mothers had several family members in their social networks with whom they had frequent contact during the past month. No differences were found between the groups on the number of family members who gave emotional sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 17 publications
6
49
0
2
Order By: Relevance
“…A social network is known to provide one with comfort and security (Hirsch, 1981;Lin & Peek, 1999). Thus, having little or no social network available tends to decrease levels of security, increasing the risk for victimization (Barnett, Martinez, & Keyson, 1996;Coohey, 2007). Social networks also seem to affect perpetration.…”
Section: Factors Affecting Ipvmentioning
confidence: 99%
“…A social network is known to provide one with comfort and security (Hirsch, 1981;Lin & Peek, 1999). Thus, having little or no social network available tends to decrease levels of security, increasing the risk for victimization (Barnett, Martinez, & Keyson, 1996;Coohey, 2007). Social networks also seem to affect perpetration.…”
Section: Factors Affecting Ipvmentioning
confidence: 99%
“…Isolation from social support networks has been documented in several studies (e.g., El-Bassel, Gilbert, Rajah, Foleno, & Frye, 2001;Thompson et al, 2000). One within-group study found more severely abused women were more isolated (Coohey, 2007). They had smaller support networks, less frequent contact with their supporters, and fewer long-term friends; this suggested that men who perpetrate severe abuse may be more successful in isolating women from their networks.…”
Section: Current Support Networkmentioning
confidence: 93%
“…A social network is known to provide one with comfort and security (Hirsch, 1981;Lin & Peek, 1999). The presence of a social network to provide social or emotional support to the individual or family can be important for Latino families; however, often a social network can lead to increased exposure and support of IPV (Barnett, Martinez, & Keyson, 1996;Coohey, 2007). Social networks also seem to affect perpetration.…”
Section: Cultural Influences and Acculturationmentioning
confidence: 99%